Affordable Technology for Enumeration of the Absolute CD4 T-Lymphocyte Count by Cell Bead Assay - Nantakomol, D; Chanprasert, S; Soogarun, S; Imwong, M; Ohashi, J; Nuchnoi, P (2010)
The quantitative BD Trucount (San Jose, CA) tube method is the conventional but expensive method to quantitate CD4+T-lymphocyte (CD4) counts, and this may be beyond the means of countries with limited resources. In this study, we validated a quantitative method known as a cell-bead (CB) assay to quantitate CD4 counts in the peripheral blood of healthy subjects. The absolute CD4 count obtained from the CB method was highly correlated with those obtained from the Trucount tube (r2=0.98, y=26.73+1.01x, P<0.0001 and a mean bias of 34.8 cell/μL, limit of agreement [LOA] -34.8-104.4 cell/μL) and flow rate-based assay method (r2=0.97; y=69.51 + 0.88x, P<0.0001 and a mean bias -53.5 cell/μL, LOA -149.4-42.3 cell/μL). This study demonstrates that the CB method is suitable and more affordable for CD4 quantitation. This method is inexpensive and interchangeable with the latex bead-based methods for generating absolute counts in resource-limited areas.